Pendampingan Warga Binaan Pemasyarakatan (WBP) Melalui Model Direct-Counter Apart Training (D-CAT) sebagai Upaya Mengurangi Pengangguran di Masa Pandemi Covid-19 di Rutan Kelas II B Buntok Kabupaten Barito Selatan - Yunitha Yunitha; Mandarin Guntur (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
One of the contributors to the unemployment is from the Warga Binaan Pemasyarakatan (WBP) including from Rutan Class II Buntok. In line with the function of RUTAN to prepare WBP to be able to integrate excellent social relationships with the community and to play a role as a free and responsible member of society, coaching and skills training for WBP were conducted. This mentoring activity aims to provide skills for WBP as carpenters in the construction business sector, especially in the South Barito district. The training applied the Service Learning (SL) method which was modified into Direct-Counter Apart Training (D-CAT), a model based on the assumption of limited time and togetherness caused by covid-19 and the status of WBP residents who have limited time to leave the room and in groups. The results showed that the WBP developed personal skills and were ready to enter the world of work, especially in the wood construction sector.